2016
DOI: 10.1111/flan.12238
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Skills and Traits of Principals in One‐Way and Two‐Way Dual Immersion Schools

Abstract: This study considers the opinions of dual immersion elementary school principals in investigating the following research questions: (1) What do dual immersion principals identify as the skills and traits for the school leader that lead to the principal's success in a dual immersion context? and (2) What were the differences of opinion, if any, between principals of one‐way and two‐way dual immersion programs about the traits and skills required for the school leader? Data was collected from 12 interviews and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 16 publications
(28 reference statements)
2
28
0
3
Order By: Relevance
“…Examinations of the meso (institutional) or micro (individual) level have often focused on singular groups. For example, studies have looked at immersion school teachers (Walker & Tedick, ) or principals (Rocque, Ferrin, Hite, & Randall, ) and the challenges they face, parents who choose dual‐immersion schools (Parkes, ; Whiting & Feinauer, ), or students in bilingual education programs (Merisuo‐Storm, ); however, studies have rarely looked across groups or within a single school environment. To better understand the ecology of language teaching and learning, the Douglas Fir Group () recommended that researchers investigate language learning in the United States today as it is situated within layered, interconnected, and complex levels—that is, to understand the discourses that are produced across school actors (micro level) and within school environments (meso level) as well as how these discourses interact with larger societal discourses (macro level).…”
Section: Introductionmentioning
confidence: 99%
“…Examinations of the meso (institutional) or micro (individual) level have often focused on singular groups. For example, studies have looked at immersion school teachers (Walker & Tedick, ) or principals (Rocque, Ferrin, Hite, & Randall, ) and the challenges they face, parents who choose dual‐immersion schools (Parkes, ; Whiting & Feinauer, ), or students in bilingual education programs (Merisuo‐Storm, ); however, studies have rarely looked across groups or within a single school environment. To better understand the ecology of language teaching and learning, the Douglas Fir Group () recommended that researchers investigate language learning in the United States today as it is situated within layered, interconnected, and complex levels—that is, to understand the discourses that are produced across school actors (micro level) and within school environments (meso level) as well as how these discourses interact with larger societal discourses (macro level).…”
Section: Introductionmentioning
confidence: 99%
“…Rocque et al (2016) have identified several skills, traits, and roles associated with successful FLIP leadership. These include knowledge of curriculum, instruction, and assessment, knowledge of language and culture, flexibility, time management, negotiation, recruiting, and soft skills such as positive and passionate, and empathic (Rocque et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rocque et al (2016) have identified several skills, traits, and roles associated with successful FLIP leadership. These include knowledge of curriculum, instruction, and assessment, knowledge of language and culture, flexibility, time management, negotiation, recruiting, and soft skills such as positive and passionate, and empathic (Rocque et al, 2016). Principals facilitate the integration of immersion teachers into the faculty and collaboration with non‐immersion teachers in professional learning communities (PLCs) (Rocque et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations